Comparing the Effects of Landscape Fragmentation by Forestry and Agriculture on Predation of Artificial Nests - Erin M. Bayne; Keith A. Hobson (Conservation Biology, 1997)
Fragmentation of forested landscapes can reduce the reproductive success of birds occupying residual forest patches. Previous studies, however, have focused primarily on how nest predation can change when landscapes become fragmented by agriculture rather than by logging. To determine if predation on artificial nests in forest patches was influenced by the surrounding landscape, we placed ground and shrub nests along the edge and interior of forest patches located in agricultural, logged, and contiguous forest landscapes within a single region of the southern boreal mixedwood forest of central Canada. Nest predators were identified using remotely triggered cameras and by marks left in plasticine eggs, whereas the relative abundance of nest predators such as corvids and small mammals was estimated by surveys and live‐trapping. The percentage of ground nests destroyed at the edge and interior of patches in the logged and contiguous forest landscapes was significantly lower than at the edge or interior of patches in the agricultural landscape. No differences in predation rate were observed for shrub nests among landscapes. We attributed higher rates of predation in the agricultural landscape to higher densities of red squirrels ( Tamiasciurus hudsonicus) in the interior and a greater diversity of predators along edges. The similarity in predation rate between logged and contiguous forest landscapes suggests that fragmentation caused by logging may result in little change in predator communities and in this respect, might be similar to fragmentation caused by natural disturbance regimes such as fire. In contrast, fragmentation by agriculture seems to have more serious consequences for nesting birds. Policy changes that limit the growth of agriculture in the southern boreal mixedwood forest are required to conserve the diverse avifauna of this region. Comparación de los Efectos de la Fragmentación del Paisaje Causada por la Acción Forestal y Agrico sobre la Depredación de Nidos Artificiales La fragmentación de paisajes forestales puede reducir el éxito reproductivo de aves que ocupan los parches residuales del bosque. Sin embargo, estudios previos se han enfocado principalmente al modo en que puede cambiar la depredación de nidos cuando los paisajes son fragmentados para agricultura en lugar de para forestería. Para determinar si el paisaje circundante influyel sobre la depredación de nidos artificiales, en parches de bosque colocamos nidos sobre el suelo y en arbustos a lo largo del borde y en el interior de parches de bosque, localizados en paisajes agrícolas, talados, de bosque continuo, en una sola región del bosque boreal mixto de Canadá central. Los depredadores de nidos fueron identificados mediante cámaras disparadas remotamente y por marcas dejades en huevos de plastilina, mientras que la abundancia relativa de depredadores de nidos como corvídos y mamíferos pequeños se estimó mediante reconocimientos y trampeos. El porcentaje de nidos sobre el suelo destruidos en el borde e interior de parches en los paisajes talados y continuos fue significativamente menor que en el borde o interior de parches en el paisaje agrícola. No se observó diferencia en las tasas de depredación de nidos en arbustos en los paisajes estudiados. Atribuimos las mayores tasas de depredación en el paisaje agrícola a la mayor densidad de ardillas rojas ( Tamiascuirus hudsonicus) en el interior y a una mayor diversidad de depredadores en los bordes. La similitud de tasas de depredación en paisajes talados y continuos sugiere que la fragmentación causada por la forestería puede producir cambios pequeños en las comunidades de depredadores y en este sentido puede ser similar a la fragmentación causada por regímenes de perturbación natural tales como fuego. En contraste, la fragmentación por agricultura parece tener consecuencias más serias para aves anidantes. Se requieren cambios políticos para limitar la expansión de la agricultura en el bosque boreal mixto para conservar la diversidad de la avifauna de esta región.